INC280 inhibits Wnt/β-catenin and EMT signaling pathways and its induce apoptosis in diffuse gastric cancer positive for c-MET amplification - Sung-Hwa Sohn; Bohyun Kim; Hee Jung Sul; Yoo Jin Kim; Hyeong Su Kim; Hongtae Kim; Jong Bok Seo; Youngho Koh; Dae Young Zang (BMC Research Notes, 2019)
Abstract Objective Gastric cancer is more open related to genetic predisposition. In our RNA sequencing study on gastric cancer patients, Runt-related transcription factor-3 (RUNX3) expression was significantly down-regulated in gastric cancer. We showed that decreased levels of RUNX3 are significantly associated with c-MET (r = − 0.4216, P = 0.0130). In addition, c-MET expression is a candidate for targeted therapy in gastric cancer. Therefore, in the present study, the anti-cancer effects of the c-MET inhibitor on gastric cancer cells from positive or negative for c-MET amplification were evaluated. Results INC280 treatment inhibits growth of a c-MET-amplified MKN45 (RUNX3-positive) and SNU620 (RUNX3-negative) diffuse type cells. Then, INC280 showed the highest inhibition and apoptotic rates with the lowest IC50s in MKN45 cells but not in c-MET-reduced MKN28 (intestinal type) cells. We also showed that INC280 inhibits the WNT signaling pathway and SNAIL expression in MKN45 cells. The data indicate that INC280 could be used as therapeutic agents for the prevention or treatment of diffuse gastric cancer positive for c-MET amplification.